Дослідження взаємодії електромагнітного поля з ґрунтом - Єніна, І. І.; Enina, І. (КНТУ, 2016)
В роботі запропоновано та досліджено використання нормальних хвиль до поверхні ґрунту. Основними інформативними параметрами при цьому є характеристики середовища: діелектрична проникність і кут падіння електромагнітної хвилі. Характеристиками взаємодії електромагнітної хвилі з поверхнею ґрунту є коефіцієнт відбиття та коефіцієнт проходження електромагнітних хвиль. При цьому, джерело та приймач випромінювання можуть бути об’єднані в одній приймально- передавальній антені. Interaction of electromagnetic waves and environment was considered to develop means of one-sided access radio waves control. On irradiation of system surface reflection and refraction of radio waves are observed at the boundary of air and environment. Here the law of reflection is fulfilled. Amplitude coefficient of electromagnetic waves reflection and passage to the plain interface of air and environment is determined by Fresnel equation. The basic information-bearing parameters here are environmental characteristics, in particular, dielectric permittivity and electromagnetic waves incidence angle. The characteristic of electromagnetic wave and soil surface interaction is the coefficient of electromagnetic waves reflection and the coefficient of electromagnetic waves passage. It is desirable to use normal waves to the surface of soil to reduce the interfering factor effect as the formula shows. Upon that the source and receiver of radiation can be combined in one receiving-transmitting antenna.
Research of electromagnetic field and soil interaction
Keywords: ґрунт; електромагнітне поле; діелектрична проникність; електромагнітні хвилі; коефіцієнт відбиття; параметр оптимізації; soil; electromagnetic field; dielectric permittivity; electromagnetic waves; reflection coefficient; optimization parameter